Geography and ethics I: Waiting and urgency. (August 2015) - Olson, Elizabeth
Within the context of global capitalism and late liberalism, the social and political implications of waiting have attracted particular attention from geographers. States and other powerful institutions can now maintain control over potentially unruly populations through technocratic management that appears at first glance to be ethically neutral. Wait lists and waiting rooms can mask inequalities and justify the denial of rights, and new spaces of indefinite waiting like detention centers and clandestine prisons have emerged as important state-sanctioned technologies for managing surplus people. As marginalized and abandoned people are made to wait, large-scale future events are treated with the greatest urgency. In this report, I explore the ethical implications and work of waiting in modern moral reasoning, and consider the scalar bias that is revealed in our research on bodily urgency and emergency.